2021
DOI: 10.3389/fnagi.2021.686499
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Higher Cardiovascular and Motor Coordinative Fitness on Driving Behavior Are Mediated by Cognitive Functioning: A Path Analysis

Abstract: Driving is an important skill for older adults to maintain an independent lifestyle, and to preserve the quality of life. However, the ability to drive safely in older adults can be compromised by age-related cognitive decline. Performing an additional task during driving (e.g., adjusting the radio) increases cognitive demands and thus might additionally impair driving performance. Cognitive functioning has been shown to be positively related to physical activity/fitness such as cardiovascular and motor coordi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 173 publications
(258 reference statements)
2
19
0
Order By: Relevance
“…Differential effects of different components of cognitive functioning and physical tness on other task parameters were also found for multitasking driving [11]. The results of both studies suggest that an overall task performance (across all task parameters) does not depend on a single component of cognitive functioning or physical tness but rather on combining several components.…”
Section: Unique Contributions Of Executive Functions and Physical Tne...mentioning
confidence: 62%
See 4 more Smart Citations
“…Differential effects of different components of cognitive functioning and physical tness on other task parameters were also found for multitasking driving [11]. The results of both studies suggest that an overall task performance (across all task parameters) does not depend on a single component of cognitive functioning or physical tness but rather on combining several components.…”
Section: Unique Contributions Of Executive Functions and Physical Tne...mentioning
confidence: 62%
“…Therefore, it might be assumed that the effects of executive functions, motor coordinative and cardiovascular tness on cognitive-motor multitasking are interrelated. For multitask driving, it could be demonstrated that there are direct and indirect effects of motor coordinative and cardiovascular tness on multitasking performance [11]. Both physical tness components were related to executive functions, directly affecting multitasking driving.…”
Section: Interplay Of Physical Tness and Executive Functionsmentioning
confidence: 99%
See 3 more Smart Citations